P3 Selective sound sensitivity syndrome (misophonia) and Tourette syndrome. Issue 10 (7th September 2012) - Neal, M; Cavanna, A E
Abstract : Objective: We present the case of a 52-year-old man first diagnosed with Tourette syndrome (TS) at the age of 44 following referral to our specialist TS clinic for chronic tic symptoms. Method: On neuropsychiatric examination, he presented with multiple motor tics (including facial grimacing and shoulder shrugging) and phonic tics (mainly yelping and barking) which were present since the age of 11. All tics were characteristically preceded by premonitory urges and he was able to voluntarily suppress them at the expense of mounting inner tension. Co-morbid psychiatric disorders included mild obsessive-compulsive behaviours (counting, lining up newspapers), previous episodes of depression and sleep problems as a child (somnambulism). Results: This patient reported being mainly distressed by what he described as functionally impairing behaviours in response to particular sounds. As a child, 1 year before developing his tics, he began experiencing annoyance at the sound of his father chewing food. Throughout his life he was affected by a range of sounds made by either familiar people or strangers with "no distinction". He would often challenge other people who might accidentally be producing such "trigger sounds", resulting in either risk taking or avoidance behaviours. These symptoms currently affect his health-related quality of life in different ways: for example, he struggles to take buses without distress and avoids them if possible because of the sounds encountered; he experiences violent thoughts towards people, to "slap or kick them, on the spur of the moment", although there is no forensic history or subjective desire to act on these impulses. Although these episodes are self-limiting on stimulus removal, functional impairment is significant given the wide range of low level, innocuous stimuli which are present in the environment. Conclusion: Selective sound sensitivity syndrome (SSSS, or misophonia, from the Greek "miso", hatred, and "phonia", sound) is described as a "hate of sound", possibly associated with abnormal activity within the limbic system and its functional connections with the primary auditory cortex and the autonomic nervous system. Misophonia is a relatively rare condition, which can be distinguished from hyperacusis by its sensitivity to the subjective response elicited. This is the first documented case of misophonia reported by a patient with a diagnosis of TS. The phenomenological similarity between misophonia and other subjective symptoms commonly reported by patients with TS (especially premonitory urges, obsessive-compulsive symptoms, not-just-right experiences) suggests a possible pathophysiological association.